The Study of Reactor Wall Fouling in Gas-solid Fluidized Beds Caused by Electrostatic Charge Generation - Sowinski, Andrew (Université d'Ottawa / University of Ottawa, 2012)
Electrostatic charge generation is unavoidable in gas-solid fluidized beds due to the repeated particle-particle and particle reactor wall contacts and separations. In industrial operations such as in polyethylene production this phenomenon results in the significant problem of reactor wall fouling, known as “sheeting”. To better understand the underlying charging mechanisms involved in gas-solid fluidized beds in an attempt to eliminate and/or reduce the effect a novel on-line electrostatic charge measurement technique was developed, which concurrently provided information on both the degree of fluidized bed electrification and reactor wall fouling. A Faraday cup replaced the windbox of the fluidized bed while another cup was placed at the top of the column. The distributor plate was uniquely designed for the systematic removal of bed particles and those adhered to the column wall for their charge measurement with the bottom Faraday cup, and the charge of the entrained particles was measured by the top Faraday cup. This is the first study which allowed the charge measurement of particles in the bulk of the bed, particles adhered to the column wall, and those entrained, simultaneously. In addition, this method uniquely permitted the evaluations of the degree of reactor wall fouling under different operating conditions. An experimental program was designed to investigate the influence of bed hydrodynamics (fluidizing gas velocity and particle size), fluidization column wall material, and the addition of different solid additives. Fluidizing particles were polyethylene resin from an industrial reactor. Bi-polar charging was observed where the elutriated particles were oppositely charged compared to those in the bulk of the bed and those adhered to the column wall. Particles within the wall coating were also found to be bi-polarly charged. With the resin tested as received, a certain sized particles (350-575 µm) adhered to the column wall. The specific charge of the particles near the column wall was found not to be a definite indication of the amount of wall fouling. Increasing the gas velocity promoted wall fouling and elevated the charge density of the particles within both bubbling and slugging flow regimes. The effect of solid additive injection was examined with two static drivers known to reduce wall fouling in industrial operations, a deactivated catalyst, and the catalyst support. It was found that the catalyst promoted, while one of the static drivers reduced wall fouling.
Keywords: Gas-Solid Fluidization; Electrostatic Charge Generation; Faraday Cup; Wall Fouling